Investigacao clinica da disfagia orofaringea - Bretan, Onivaldo [UNESP]; Tagliarini, José Vicente [UNESP] (My University, 1998)
The accurate investigation of the oropharyngeal dysphagia demands a systematic sequence of physical examinations. The aim of the present work is to propose a practical rule to facilitate the clinical investigation and the management of dysphagic patients. After a detailed anamnesis, an endoscopic examination is carried out and several manouvers to observe the oral, pharyngeal and laryngeal functions are performed by the patient. Following, a second endoscopy is performed during swallows of several consistencies of food, to verify the impairment of the laryngeal and or pharyngeal activities. The elevation of the laryngeal cartilage is also evaluated.
Clinical investigation of the oropharyngeal dysphagia
Keywords: Dysphagia; Physical examination; Protocol; anamnesis; diagnostic accuracy; dysphagia; endoscopy; human; human tissue; larynx cartilage; oropharynx; physical examination